Assessment of Psychological Risk Factors Which Contributed to the Occurrence of Peptic Ulcer in Patients at Irbil Governorate - Sheerin Aziz (Iraqi National Journal of Nursing Specialties, 2023)
Objective: An analytic- descriptive study to assess the psychological factors that may contribute to the occurrence of peptic ulcer as risk factors and to compare between studied and control groups with the impact of psychological risk factors. Methodology: A questionnaire 25 designed, which consisted two parts including sociodemographic characteristics and the 32 items to describe the psychological factors (anxiety, depression, somatoform symptoms). The sample consist of (100) patients who were admitted to the endoscopy department at two teaching hospitals (Hawler and Rezgari) in Irbil, and were diagnosed as a peptic ulcer patients; and (100) person as a control sample were selected from community and they were free of any gastrointestinal disorders. Results: The results of the study revealed that the majority of the study group was above 51 years old and above, the males were more presented than females, they were married, with low educational level, unemployed, within sufficient monthly income with insufficient and most of them were exposed to stressfill life events, also the study revealed that there was a significant relationship between psychological risk factors and the occurrence of peptic ulcer. Recommendations: The researcher recommends that nurses should be provided with the assessment tools which was used in this study, and conduct an educational program to the patient with gastrointestinal ulcer to increase their knowledge toward disease and reduce the risk of peptic ulcer disease.